DESIGN ANDROID-BASED APPLICATION OF “PERMEN” FOR MENARCHE PREPARATION FOR TEENAGE GIRLS - Susilawati, Sri; Kurniawati, Ade (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
According to Riskesdas data, menarche among adolescents aged 10–19 years typically occurs at age 12 (42.8%), age 15 (96.2%), and age 18 (99.6%). Many adolescents experience anxiety during their first menstruation due to a lack of knowledge, leaving them psychologically, mentally, and emotionally unprepared for the bodily changes. In today’s digital era, there is a growing need for accessible educational tools that provide accurate information about menstruation. To address this, an application called “Permen” (short for *Persiapan Menarche*) was developed to help adolescent girls prepare for their first menstruation anytime and anywhere. The aim of this study was to design a mobile-based menarche preparation application using the System Development Life Cycle (SDLC) method. The SDLC model applied was the waterfall model, which follows a structured, step-by-step approach in software development. The research successfully resulted in the creation of the “Permen” application, which has undergone both black box testing and expert validation. The application provides comprehensive and age-appropriate information about menarche, helping reduce anxiety and increase awareness among adolescent girls. In conclusion, the “Permen” application serves as a practical educational tool to support young girls during the transition of puberty by improving their readiness and understanding of menstruation.